EMBEDDING ISLAMIC ETHICAL VALUES IN TEACHERS’ TRAINING PROGRAM: QUR’ANIC APPROACH - Ahmed Mohamed, Ismaiel Hassanein; Rawash, Fouad Mahmoud (2019)
Islamic Value is the highest ethical manner of mankind on the earth, concerning man’s behaviours and actions- orally and verbally, it is because of originality and authentication. Value in Arabic term refers to akhlaq and adab. These Islamic Values comprising certain essential moral, ethical, cultural, social, and spiritual values. Such values are important and necessary for children through their all-round development and prepares them as a complete man. The aim of this paper is to overlook the current various ethical issue existing in Muslim communities around the world, the importance of teachers’ rule in inculcating moral values in their students, and to suggest a framework for Islamic Values education to be embedded in the curriculum of Higher Learning Institutions catered for pre-service teachers as part of ethical/moral training before they start their career. To achieve its aim, the paper is based on a descriptive method to describe the Ethical/moral Values from Islamic and non- Islamic perspectives based on current research available on line or/and offline. The focus is on the Quranic approach, specifically stated in surah al-Isra’, verses 22-39 and surah al-An’am, verses 151-153. The finding is expected be used as a guideline for Ethical values course/topics that embedded in Teachers’ training programs.